KNOWLEDGE AND PHYSIOLOGICALLY EFFECTS OF TAPEL TOWARDS POSTPARTUM MOTHERS (Journal of Engineering and Health Sciences, 2020)
Maternity period is a crucial transition period for mothers, which had affected them emotionally and socially. Within postpartum period, there will be some physiology changes such as involution (shrinking or return of an organ to a former size). The use of ‘Belly Tapel’ which is believed can rescued mothers’ physiology to returned back as before. This research aims to study the correlation of knowledge and the use of ‘Belly Tapel’ towards maternity mothers’ physiologically. This study was conducted in Indonesia (location: Langkat, Deli Serdang and Medan), where the sample of maternity mothers with 25-39 years old who have ever used ‘tapel’ (74 people) was collected. Correlation test and T-test were conducted in this study. To analyze the effect of tapel used towards mothers’ physiology was also conducted from day 0 until day-40 by measuring mothers’ weights and waist size changes. Based on the result, it was found that there were correlation (p